PELAKSANAAN FISIOTERAPI PADA KASUS POST OPERASI TOTAL KNEE REPLACEMENT - Amelia Fadlina; Nila Kusma; Vina Wulandari (Jurnal Real Riset, 2022)
This study aims to determine; (1) Can Infrared (IR) modality improve blood circulation and reduce pain? (2) Knowing whether exercise therapy can increase muscle strength. (3) Whether exercise therapy can increase the strength of the Joint Scope of Motion by using a Goniometer. This research is a qualitative research with a case study design, namely to determine: (1) Whether the Infrared (IR) modality can improve blood circulation and reduce pain. (2) Knowing whether exercise therapy can increase muscle strength. (3) Whether exercise therapy can increase the strength of the Joint Scope of Motion by using a Goniometer. The subjects in this study were patients who complained of pain, muscle weakness, and joint limitations in the patient's knees. The research subject consisted of one person. Data were obtained by conducting interviews, observations and physiotherapy management actions in postoperative cases of total knee replacement. Based on the results of the research that has been done, the results show that after intervention with infrared (IR) modalities, and exercise therapy with a frequency of 6 consecutive treatments. It was found that there was a decrease in pain, an increase in muscle strength in the right knee, and an increase in the range of motion of the knee joint.Keywords: Physiotherapy management, postoperative total knee replacement cases